In the presence of Sai Baba : body, city, and memory in a global religious movement - Srinivas, Smriti. (Numen Book Series, 2008)
The Sai Baba movement, centered on the Indian guru Sathya Sai Baba (b. 1926), today attracts a global following from Japan to South Africa. Regarded as a divine incarnation, Sathya Sai Baba traces his genealogy to Shirdi Sai Baba (d. 1918), a mendicant in colonial India identified with various Sufi and devotional genealogies. The movement, thus, has "roots" in Shirdi Sai Baba but as it globalizes, it has developed conjunctions with other religious traditions, New Religious movements, and New Age ideas. This book offers an account of the Sai Baba movement as a pathway for charting the varied cartographies, sensory formations, and cultural memories implicated in urbanization and globalization. It traverses the terrain between social theories for the study of religion and cities ---themselves a product of modernity---and the radical, creative, and unexpected modernity of contemporary religious movements. It is based on ethnographic research carried out in India, Kenya, and the US.